2005
DOI: 10.1177/107769580506000110
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Print, Broadcast, and Online Journalism Concurrently: A Case Study Assessing a Convergence Curriculum

Abstract: About 60% of U.S. journalism schools are preparing students to work across multiple media platforms. In fall 2002, the University of Southern California launched a Convergence Core Curriculum (CCC) in which all journalism students learned print, broadcast, and online journalism concurrently. Both students and instructors reported that the classes slowed the learning process, and that class content was diluted. However, students nevertheless showed marked improvement in key skills. These results and a review of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…6 Castaneda et al found technological advances and the new media landscape were the two major catalysts for change at journalism schools. 7 Between 1998 and 2002, 60 percent of journalism schools in the United States were redesigning their curricula or developing new courses to prepare students for producing news in multiple media platforms. 8 Criado and Kraeplin surveyed 240 journalism programs and found that nearly 85 percent had adopted a convergence curriculum in response to the industry emphasis on convergence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…6 Castaneda et al found technological advances and the new media landscape were the two major catalysts for change at journalism schools. 7 Between 1998 and 2002, 60 percent of journalism schools in the United States were redesigning their curricula or developing new courses to prepare students for producing news in multiple media platforms. 8 Criado and Kraeplin surveyed 240 journalism programs and found that nearly 85 percent had adopted a convergence curriculum in response to the industry emphasis on convergence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, Internet news is becoming more popular wherever the public has wide and easy access to the Internet, because news in this medium is updated dynamically (Yau and Al-Hawamdeh 2001). The curriculum on journalism education has changed as a result, and students are now required to develop cross-platform skills in universities (Castañeda, Murphy, and Hether 2005). While the craft of writing and reporting is essential for success in journalism, graduates are also expected to be proficient in oral and written communication and technically competent in the digital newsroom when they move into their future careers.…”
Section: Introductionmentioning
confidence: 99%
“…Like the curriculum, the syllabus is a specific textual genre with distinctive normative rhetorical characteristics but is more closely connected to the substance area of teaching and operates at a more concrete level of teaching methodology and learning contents (Afros and Schryer 2009;Nunan 1998;Robinson 2012). Journalism scholars typically have had less interest in syllabus design but have studied curricula in relation to journalism education, particularly curriculum development, priorities in teaching content, interactions with the industry and media environment and motivations from technological development (see e.g., Adams 2008;Blom and Davenport 2012;Castañeda, Murphy, and Heather 2005;Hirst and Treadwell 2011). Syllabi have a higher formal status than lesson plans, which set the outline of an individual lecture or describe the set of lectures that form a course or a course entity.…”
Section: Course Syllabi and The Politics Of The Production Of Educationmentioning
confidence: 99%